The City after Property : Abandonment and Repair in Postindustrial Detroit - Safransky, Sara (Book collections on Project MUSE., 2023)
"In The City after Property, Sara Safransky examines how postindustrial decline generates new forms of urban land politics. In the 2010s, Detroit government officials classified a staggering 150,000 lots-more than a third of the city-as "vacant" or "abandoned." Analyzing subsequent efforts to shrink the Motor City's footprint and budget, Safransky presents a new way of conceptualizing urban abandonment. She challenges popular myths that cast Detroit as empty and narratives that reduce its historical decline to capital and white flight. By connecting contemporary debates over neoliberal urbanism to Cold War histories and the lasting political legacies of global movements for decolonization and Black liberation, she foregrounds how the making of-and challenges to-modern property regimes have shaped urban policy and politics. Drawing on critical geographical theory and community-based ethnography, Safransky shows how private property functions as a racialized construct, an ideology, and moral force that shapes selves and worlds. By thinking the city "after property," Safransky illuminates alternative ways of imagining and organizing urban life"--